Affirming Human Equality Through Taqwa: A Thematic Interpretation Study of QS. Al-Hujurat Verse 13 - Haqim, Fathir Nur Muhammad; Atiq, Dewi Shinta Baitul; Al Huda, M. Ibnu Wahid; Nur Aini, Fatimatul Nirma (Institut Agama Islam Negeri Kediri, 2025)
QS al-Ḥujurāt [49]:13 is frequently invoked in discussions of ethical equality, particularly amid contemporary tensions involving race, class, and identity. Despite its prominence, studies that examine how the concept of taqwa is systematically constructed as a normative foundation for egalitarianism remain limited. This gap frames the present inquiry. Employing a qualitative library-based approach, the study applies thematic exegesis and comparative analysis to Anwār al-Tanzīl and Taysīr al-Karīm al-Raḥmān. The analysis proceeds through mapping the exegetical arguments, identifying hermeneutical divergences, and synthesizing their social and conceptual implications. Findings indicate that al-Bayḍāwī conceptualizes taqwa through a filological lens while simultaneously critiquing hierarchical Arab social structures, positioning taqwa as a theological mechanism that nullifies genealogical prestige and affirms the equality of human origins. In contrast, al-Saʿdī foregrounds the social dimension of taqwa as an ethical orientation that regulates interaction, strengthens solidarity, and curbs group dominance in plural societies. These differing emphases reveal a conceptual shift from taqwa as a spiritual category to a moral principle operative within social life. The study contributes a conceptual framework linking taqwa and egalitarianism and offers an interdisciplinary vantage point for contemporary justice-oriented scholarship.